2010
DOI: 10.1590/s1516-35982010001300026
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and breeding of sheep in Brazil

Abstract: Studies in genetics and breeding of sheep in Brazil have increased significantly in recent years. These involve research in characterization, breeding and crossing sheep using new technologies available incorporating both classical quantitative and molecular genetics. Improvements in statistical techniques, computational resources as well as analysis of DNA and gaps in present knowledge and opportunities for possible research are pointed out. There is a need for greater interaction between various groups worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 58 publications
2
63
0
4
Order By: Relevance
“…This result may be due to the small sample population (15 individuals), and due to the population being consolidated with planned genetic crosses established from breeding programs. Several studies using locally adapted or native breeds confirmed that these breeds have more number of loci in HWE when compared to more specialized breeds (McManus et al, 2010;Paiva et al, 2011a;Tolone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to the small sample population (15 individuals), and due to the population being consolidated with planned genetic crosses established from breeding programs. Several studies using locally adapted or native breeds confirmed that these breeds have more number of loci in HWE when compared to more specialized breeds (McManus et al, 2010;Paiva et al, 2011a;Tolone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite data showing that several alterations outside the 136/154/171 codons, the relationship between the alteration and scrapie resistance could be speciϐic to the breed analyzed (Colussi et al 2010;McManus et al 2010). Therefore, it is vital to determine genotype for codons other than the classical ones associated with scrapie resistance and susceptibility for the different ovine breeds, establishing guidelines for genetic programmes aiming at scrapie epidemic risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…According to Paiva et al (2011), the use of only one class of marker (typically microsatellites) to inform maintenance and management policies is not desirable because one marker cannot provide all of the necessary genetic information. Studies involving Morada Nova sheep have been developed using RAPD (Paiva et al, 2005a), PCR-RFLP (Paiva et al, 2005b), microsatellites, and mtDNA (Paiva, 2005;McManus et al, 2010) markers. Paiva (2005) analyzed microsatellite genetic divergence between two herds of White and Red varieties and identified significant differences between them.…”
Section: Discussionmentioning
confidence: 99%